AULDOUS HUXLEY AND HIS DYSTOPIAN NOVEL “BRAVE NEW WORLD” (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This article offers a comprehensive examination of Aldous Huxley's seminal dystopian novel, "Brave New World." It delves into Huxley's portrayal of a future world where conformity, consumerism, and control reign supreme, contrasting it with contemporary social and political realities. By analyzing characters, themes, and narrative techniques, the article explores how Huxley's vision of a technologically driven society reflects enduring concerns about individual freedom, human nature, and the consequences of scientific advancement. Additionally, it discusses the novel's cultural impact, influencing debates on totalitarianism, genetic engineering, and the commodification of human experience. Ultimately, this article seeks to illuminate the continued relevance of "Brave New World" as a cautionary tale and a catalyst for critical reflection on the complexities of modern society.